Equity Markets, Financial Integration and Competitive Convergence - Gongyu Chen; Chris Higson; Sean Holly; Ivan Petrella (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We expect a firm's competitive advantage to manifest itself in a return on invested capital that is higher than the opportunity cost of capital. Deviations of returns from the cost of capital are a signal for competitive entry or for exit, while the speed of convergence indicates the strength of competitive forces. It is widely believed that, in some sense, the world is becoming more competitive, and that this is may be the effect of globalisation, facilitated by innovations in information technology. It also be the effect of determined actions by governments over two or three decades, to deregulate and open up markets to competition. So for example, in Europe one purpose of both the common currency and the Single Market project was to accelerate the process of economic convergence and, presumably, of competitive convergence. This paper examines the process of competitive convergence in profitability of listed companies in 7 countries of the European Union. We cast our examination of the convergence process in terms of three questions. The first is whether, and to what extent, we observe convergence in profitability through time. The second question is whether there are national differences in the extent of convergence or the speed at which it takes place. Thirdly, we look at the dynamics of convergence through time to see whether there is evidence that convergence in profitability has become more rapid, by which we mean above average or below average profitability persists for a shorter space of time because of increases in competition. The extent to which this can be related to economic and monetary convergence in the European Union remains an open question.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: 330; Markov processes; profitability; competitive convergence